Formula-Based Software Debugging. - ROYCHOUDHURY, ABHIK; CHANDRA, SATISH (Communications of the ACM, 2016)
The article discusses the use of satisfiability modulo theory solvers in formula-based software debugging as form of computer-assisted debugging. Topics include the use of symbolic techniques to extract candidate specifications, the use of an Address Resolution Protocol (ARP) implementation, and the use of interpolants to find error root-causes.